(untitled) (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2021)
Sustainable development, reduction of energy consumption and more intensive use of renewable energy sources represent a challenge and one of the goals of the energy policy of the Republic of Serbia. The changes in the household management referring to energy-saving behavior imply environmental awareness of consumers and continuous change of their habits with the aim of sustainable energy use and the transition to greater use of renewable energy sources. Subjective norms represent a variable that has a significant impact on the energy-saving consumer behavior. The purpose of this paper is to analyze subjective norms in the context of energy efficient behavior and more intensive use of renewable energy sources. The objective of this paper is to identify the impact of subjective norms on the use of solar panels in the Republic of Serbia in the context of socio-demographic characteristics of consumers, based on the results of empirical research. The measurement of subjective norms regarding solar panels was performed on the basis of the grades obtained on a five-point Likert scale, and the comparison of respondents with different sociodemographic characteristics was done using the SPSS software package. The results of the research show the influence of subjective norms on the intention to introduce the use of solar panels in the households in the Republic of Serbia.